Pengaruh SCAMPER Project Teaching Berbantuan AR Terhadap CSE, CPI, Dan Penguasaan Konsep Siswa SD - Maulana Tri Wijayanti (Jurnal Ilmu Pendidikan, 2026)
This study was motivated by the low levels of Creative Self-Efficacy (CSE), Creative Personal Identity (CPI), and concept mastery among students at SD Negeri Bantulan due to conventional, teacher- and textbook-centered learning. This study aimed to describe the implementation of Augmented Reality (AR)-assisted SCAMPER Project Teaching on the theme of Man-Made Environment, and to analyze its effect on CSE, CPI, concept mastery, and student responses among fifth-grade elementary school students. This research employed a quantitative approach with a quasi-experimental method using a Pretest-Posttest Nonequivalent Control Group design, involving class V A (20 students) as the experimental group and class V B (17 students) as the control group. Data were collected through observation, questionnaires, and tests, then analyzed descriptively and inferentially using the Independent Sample t-test and the Mann-Whitney U test. The results showed that the implementation of learning was very good in both the experimental (89.61%) and control (85.84%) classes. The N-gain of CSE and CPI in the experimental class (0.26 and 0.17) was descriptively higher than in the control class (0.17 and 0.09), but the difference was not statistically significant (CSE: p=0.075; CPI: p=0.181). Regarding concept mastery, the N-gain of the control class (0.048) was slightly higher than that of the experimental class (0.028) and was also not significant (p=0.972). Student responses were in the good category in both classes (experimental 80.92%; control 77.35%). It is concluded that AR-assisted SCAMPER Project Teaching was implemented very well and received a positive response from students, but had no significant effect on students' CSE, CPI, or concept mastery in this study.